TNF-ɑ Induces Methylglyoxal Accumulation in Lumbar Herniated Disc of Patients With Radicular Pain - Zhang, Xinsheng; Wang, Xiaogang; Gao, Liang; Yang, Bin; Wang, Yahan; Niu, Kerun; Lai, Jiahui; Wan, Shun; Luo, Jianping (Frontiers in Behavioral Neuroscience, 2021)
Lumbar disc herniation (LDH) with radicular pain is a common and complicated musculoskeletal disorder. Our previous study showed that LDH-induced methylglyoxal (MG) accumulation contributed to radicular pain. The underlying mechanisms through which MG accumulates are poorly understood. In the present study, we found that both MG and TNF-ɑ levels in herniated disc of patients with radicular pain were significantly increased and the activity of Glyoxalase 1 (GLO1), the rate-limiting enzyme that metabolizes MG, was decreased. In rats, LDH model was mimicked by implantation of autologous nucleus pulposus (NP) to the left lumbar 5 spinal nerve root. The mechanical allodynia was observed in LDH rats. Besides, MG and TNF-ɑ levels were increased, and GLO1 activity was significantly decreased in the implanted NP. In cultured rat NP cells, stimulation with the inflammatory mediator TNF-ɑ reduced GLO1 activity and expression. These results suggested that TNF-ɑ-induced GLO1 activity decrease contributed to MG accumulation in herniated disc of patients with radicular pain.